1995
DOI: 10.1038/ki.1995.310
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C signals thromboxane induced increases in fibronectin synthesis and TGF-β bioactivity in mesangial cells

Abstract: Previous studies have demonstrated that thromboxane (TX) stimulates matrix protein synthesis in mesangial cells (MC), and that this action is signalled by receptor mediated activation of protein kinase C (PKC). In the present study, we examined the hypothesis that activation of PKC by TX signals increases in transforming growth factor beta (TGF-beta) bioactivity, which in turn induces enhanced matrix protein synthesis. In cultured rat MC, the TXA2/prostaglandin endoperoxide analogue U-46619, but not exogenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 44 publications
0
39
0
Order By: Relevance
“…TGF-␤ mediates increases in collagen synthesis induced by other G-protein-coupled receptor agonists, including angiotensin II (40) and thromboxane (41). We determined the amount of active TGF-␤ present in the culture medium from untreated and des-Arg 10 -kallidin-treated fibroblasts using the bioassay in which MLEC growth was inhibited in a dose-dependent manner by active TGF-␤.…”
Section: Resultsmentioning
confidence: 99%
“…TGF-␤ mediates increases in collagen synthesis induced by other G-protein-coupled receptor agonists, including angiotensin II (40) and thromboxane (41). We determined the amount of active TGF-␤ present in the culture medium from untreated and des-Arg 10 -kallidin-treated fibroblasts using the bioassay in which MLEC growth was inhibited in a dose-dependent manner by active TGF-␤.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was shown that normalizing levels of mitochondrial reactive oxygen species prevents the three major pathways caused by hyperglycemia: PKC, advanced glycation end products (AGEs), and the aldose reductase pathway (Nishikawa et al, 2000). PKC and AGEs have been shown to increase TGF-␤ expression in mesangial cells (Yang et al, 1994;Studer et al, 1995). Oxidative stress might stimulate TGF-␤-stimulated matrix synthesis in the glomeruli through the activation of PKC and AGE-mediated pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of Ang II to AT1 receptor stimulates PI-PLC, increases protein tyrosine phosphorylation, and activates Ras and several protein kinases, such as PI3K, PKC, MAP kinase, Ca 2ϩ /calmodulin kinase, and S6K (24,74). Previous studies propose an important role for PKC as an intracellular mediator of the effects of several hypertrophic growth stimuli (22), including mesangial cell FN production (75). In this study, we showed that Ang II-mediated expression of FN mRNA was inhibited by PKC inhibitors, suggesting that activation of PKC is involved in Ang II responses.…”
Section: Fig 8 Effect Of Inhibitors Of Pi-plc G I Ras Map Kinasmentioning
confidence: 99%